Legal Legality of Pregnant Marriage in Indonesia Study on the Application of Khi Article 53 in Mlati District Prospective Fatwa Abno Taymiyah - Binarsa Binarsa (Publikasi Indonesia, 2024)
Formulating the Compilation of Islamic Law is inseparable from the growth and development of Islamic law and the institution of the Religious Courts before and after the Indonesian people proclaimed their independence on August 17, 1945. So the Indonesian people who are Muslim, The Religious Courts, the Ulama, and all components related to the determination of KHI agree that the compilation of Islamic Law is Islamic law, which is the source of law to solve the problem of pregnant marriage in Indonesia. However, in the day-to-day application of this decree, an interesting problem occurred, which was partly that the Mlati community did tajwid al-Nikah. A question! Why did they remarry? They answered that because they considered the marriage they were having at KUA, there were doubts, and they were not legal.